Brutplatzqualität unterschiedlich ökologisch bewirtschafteter Ackerfrüchte für die Feldlerche (Alauda arvensis) - Neumann, Dr. Helge; Loges, Dr. Ralf; Taube, Prof. Dr. Friedhelm (2009)
Habitat quality of different arable crops for skylarks (Alauda arvensis) was analysed in a three year field study on 12 organic farms in northern Germany. Grass clover, spiked spring cereals (barley/spelt/wheat), winter wheat as well as grain legumes (including mixtures) hold constant abundances of skylarks during the whole breeding period. In spring oats, winter spelt and winter cereals with awn (barley/rye), however, skylark densities decreased during the breeding time, which might be explained by comparatively taller and/or denser vegetation structure of theses crops during June/July. Crops showed no significant differences in maximum abundances of skylarks. Concerning possible effects on breeding success, harrowing and/or hoeing of cereals and grain legumes should be completed as early as possible in spring to prevent breeding losses. Compared to cereals and grain legumes, the management of grass clover crops probably resulted in higher breeding losses due to a high intensity of mowing. While the cutting regime of grass clover used as green manure crops can be adapted to breeding phenology of skylarks, modification of cutting systems of forage crops should cause negative effects on quality of forage.